Plasmodium vivax Pv12 B-cell epitopes and HLA-DRβ1*-dependent T-cell epitopes in vitro antigenicity (2018)
Malaria is an infectious disease caused by parasites from the genus Plasmodium (P. falciparum and P. vivax are responsible for 90% of all clinical cases); it is widely distributed throughout the world’s tropical and subtropical regions. The P. vivax Pv12 protein is involved in invasion, is expressed on merozoite surface and has been recognised by antibodies from individuals exposed to the disease. In this study, B- and T-cell epitopes from Pv12 were predicted and characterised to advance in the design of a peptide-based vaccine against malaria. For evaluating the humoral response of individuals exposed to natural P. vivax infection from two endemic areas in Colombia, BepiPred-1.0 software was used for selecting B-cell epitopes. B-cell epitope 39038 displayed the greatest recognition by naturally-acquired antibodies and induced an IgG2/IgG4 response. NetMHCIIpan-3.1 prediction software was used for selecting peptides having high affinity binding for HLA-DRβ1* allele lineages and this was confirmed by in-vitro binding assays. T-epitopes 39113 and 39117 triggered a memory T-cell response (Stimulation Index2) and significant cytokine production. Combining in-silico, in-vitro and functional assays, two Pv12 protein regions (containing peptides 39038, 39040, 39113 and 39117) have thus been characterised as promising vaccine candidates against P. vivax malaria. © 2018 Yepes-Pérez et al. This is an open access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited.